Inovasi Gummy Sehat: Kontribusi Mahasiswa Kuliah Kerja Nyata (KKN) Universitas Muhammadiyah Bandung dalam Upaya Pencegahan Stunting di Desa Bongkok: Pengabdian - Humaira Andini Putri; N.Samrothuldini; Kiki Sulistiya Rini; Fajri Rozikin; Dina Marlina; Meilanie Tri Pratiwi; Raisya Kirana; Reynaldi Continenta Putra; Wilby Abdurahman May; Zaydan Muhammad Najib; Hani Humaeriyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Stunting remains a serious health problem in Indonesia, particularly in Sumedang Regency, which has a high prevalence rate of 27.6% according to the 2022 SSGI. One of the factors contributing to stunting is low appetite in children, which leads to inadequate nutrient intake. Through the Community Service Program (KKN) of Muhammadiyah University of Bandung, an innovation was developed to create healthy snacks in the form of gummies made from natural ingredients such as ginger, turmeric, citrus, honey, and gelatin. This program was packaged in the form of socialization and workshops with the women of the Bongkok Village PKK, with the aim of providing education and practical skills in processing spices into functional products. The results of the activity showed high enthusiasm from the participants, active involvement in the manufacturing process, and positive acceptance of the gummy as a healthy snack to increase children's appetite. This innovation is expected to support stunting prevention efforts while opening up opportunities for community economic empowerment.